Bibliometric Analysis of CEFR-Based Strategies in University-Level Speaking Instruction - Tuilan, Jeane; Widodo, Pratomo; Putro, Nur Hidayanto Pancoro Setyo; Tuerah, Ignatius Javier C.; Mahayanti, Ni Wayan Surya (Journal of Ecohumanism, 2025)
A bibliometric analysis was conducted on CEFR-based strategies in university-level speaking instruction, based on data from 43 publications from 2014 to 2024. The CEFR’s significant global influence on curriculum design, teaching methodologies, and assessment practices was substantiated. The data revealed an increase in the number of publications in 2016, 2019, and 2022, with a decline in other years. This pattern is likely influenced by external factors, such as the impact of the global pandemic caused by the SARS-CoV-2 virus. The primary focus was on linguistic and cultural dimensions, with "Language Communication and Culture" representing the most highly-cited publication. The most frequently cited sources, such as "Speaking Teaching" and the "International Journal of Emerging Technologies in Learning (iJET)," emphasized the integration of technology in language instruction. Co-authorship analysis revealed the existence of well-established regional collaborative networks, which underscored the importance of collaborative efforts. The analysis confirmed the CEFR’s enduring impact on speaking education and identified trends and gaps, which highlighted the need for greater international collaboration and diversity to enhance effective language teaching practices and inform policy decisions.